The Effects of ZnO particles on the color homogeneity of phosphor-converted high-power white LED light sources - Nguyen Thi Phuong Loan; Nguyen Doan Quoc Anh (Institute of Advanced Engineering and Science, 2020)
Color homogeneity is one of the goals to continuously improve WLED. Among the methods for enhancing the color uniformity of WLEDs, improving scattering in phosphor layer is considered to be the most effective. In this paper, ZnO is used for that purpose. The results show that ZnO particle size significantly affects scattering in the phosphor layer, which is a vital factor to analyze scattering, scattering sand surface, scattering coefficient and scattered phase function C_sca (D,λ), μ_sca (λ) and ρ(θ,λ). In addition, the concentration of ZnO was also analyzed with values from 2% to 22%. Color homogeneity depends not only on size but also on the concentration of added ZnO. Therefore, color homogeneity control is the control of ZnO size and concentration. The proposed result is 10% ZnO for the highest lumen of LED. With 14% and 500 nm of ZnO particles, ΔCCT reaches the lowest. Depending on the production needs, manufacturers can choose the most appropriate way. However, with both required lumen and ΔCCT, 14% ZnO is suitable for ZnO sizes.